2019
DOI: 10.1039/c8ta10337b
|View full text |Cite
|
Sign up to set email alerts
|

Achieving long-term anticorrosionviathe inhibition of graphene's electrical activity

Abstract: Novel B-doped functionalized graphene: an excellent filler for enhancing the long-term barrier properties of polyurethane coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…Similar studies suggested that the incorporation of graphene (generally, >0.1 wt%) in insulating polymer could increase the bulk conductivity, endowing the coatings with the unacceptable corrosion‐promotion activity. [ 10,11,16,17 ] Therefore, the corrosion protection performance of B–G–WEP coating is superior to pure WEP and R–G–WEP coatings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies suggested that the incorporation of graphene (generally, >0.1 wt%) in insulating polymer could increase the bulk conductivity, endowing the coatings with the unacceptable corrosion‐promotion activity. [ 10,11,16,17 ] Therefore, the corrosion protection performance of B–G–WEP coating is superior to pure WEP and R–G–WEP coatings.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] During the past decade, starting from the early chemical vapor deposition (CVD) graphene, various graphene‐based coatings, comprising graphene thin film coatings and graphene‐based polymer composite coatings, have been prepared and developed. [ 8–12 ] However, enhancements in dispersibility and eliminating localized galvanic corrosion (battery circuits formed at the exposed graphene–metal interface accelerate deterioration of the underlying metal) are needed before graphene can be employed for fabricating high‐performance and long‐lasting anticorrosion coatings. [ 13–15 ] According to the previous works, [ 2,16–18 ] the insulating encapsulation with polymers is an effective strategy to achieve the good dispersion and inhibit corrosion promotion activity of graphene coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[14,204] By utilizing graphene or its derivatives as nanometric fillers in the polymeric matrix, it is possible to lengthen the diffusion pathway of the corrosion medium in the coatings by taking advantage of its chemical inertness and barrier properties. [13] Graphene has heretofore been combined with a wide variety of polymeric materials, such as epoxy (EP), polyurethane (PU), [254][255][256][257][258][259] polyaniline (PANI), [227,233,[260][261][262] alkyd, [263] polystyrene (PS), [264] PMMA, [265,266] polyvinyl butyral (PVB) and [267,268] polydimethylsiloxane (PDMS). [269] The lack of functional groups on the surface of pure graphene, its high surface area (and, consequently, high surface energy) and the Van der Waals interactions pose major challenges for the dispersion of graphene as filler particles in coating matrices, resulting in poor compatibility.…”
Section: Dispersion In Polymeric Matricesmentioning
confidence: 99%
“…Taking into consideration the fact that highly conductive graphene can aggravate localized corrosion at exposed metal-coating interfaces, several efforts have been made to suppress its undesired corrosion-promotion effect. [226,259,260,268] Contrarily, other authors have taken advantage of such feature to mitigate corrosion processes on metal surfaces by incorporating graphene-based conductive additives in organic coatings. Since the 1930s, zinc-rich coatings (ZRCs) have been extensively utilized for a multiplicity of industrial purposes under a wide range of hostile conditions.…”
Section: Composites For Active Corrosion Protectionmentioning
confidence: 99%
“… [2] Therefore, in order to target the synthesis of a specific molecular structure, it is crucial to find a reaction that induces selectivity. In this work, we show that a route based on the well‐known Michael addition, [3, 4] complemented with the unique properties of metal surfaces, generates high selectivity towards nucleophilic attack at site 4 (see Scheme 1, panel b), such that starting from simple para ‐aminophenol ( p ‐AP) precursors we obtain meta ‐coupled oligomers of polyaniline (PANI).…”
Section: Introductionmentioning
confidence: 98%